Psychological Interventions to Enhance Self-Efficacy and Motivation in Libyan Students - Akram Alhamad; Abdullah Mahfoud Salem Baadhem; Abdulazeez Abed Hameed (Research Synergy Foundation, 2024)
Extensive research shows that higher self-efficacy is associated with increased motivation, perseverance, and academic success; however, there is a notable gap in understanding how these constructs interact within the unique context of Libyan higher education. This study explores the relationship between self-efficacy and motivation among university students in Libya, where cultural norms, Islamic principles, and socio-political factors deeply influence educational practices. To address this issue, the study employed a cross-sectional design and collected data through self-administered questionnaires from students at major universities in Libya. The data were analyzed using Pearson correlation and multiple regression techniques to examine the strength and direction of the relationship between self-efficacy and student motivation. The findings revealed a significant positive correlation between these two variables, indicating that students with higher levels of self-efficacy are more motivated in their academic pursuits. Furthermore, the multiple regression analysis identified self-efficacy as a significant predictor of student motivation, explaining 46% of the variance observed in the sample. These results underscore the critical role of self-efficacy in fostering student motivation within the Libyan educational context. The findings suggest that targeted interventions to enhance self-efficacy could significantly improve educational outcomes. The findings provide a foundation for future research and the development of educational strategies tailored to the specific needs of Libyan students, thus contributing valuable insights to the broader literature on self-efficacy and motivation in higher education.